2022
DOI: 10.3389/fcell.2022.882017
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, Expression and Functional Analysis of CXCR3 in Neuronal and Cardiovascular Diseases: A Narrative Review

Abstract: Chemokines form a sophisticated communication network wherein they maneuver the spatiotemporal migration of immune cells across a system. These chemical messengers are recognized by chemokine receptors, which can trigger a cascade of reactions upon binding to its respective ligand. CXC chemokine receptor 3 (CXCR3) is a transmembrane G protein-coupled receptor, which can selectively bind to CXCL9, CXCL10, and CXCL11. CXCR3 is predominantly expressed on immune cells, including activated T lymphocytes and natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 131 publications
1
23
0
Order By: Relevance
“…We estimated the predominant cascade of GFAP‐A and CNS‐irAE by examining the chemokine profile of CSF. In this study, the chemokine profile demonstrated the following: CNS‐irAE as Th1‐predominant diseases as reported previously 9–13,26 . GFAP‐A was the first to demonstrate a predominance of Th1 + Tfh/B cells, suggesting that cellular immunity is important in its pathogenesis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We estimated the predominant cascade of GFAP‐A and CNS‐irAE by examining the chemokine profile of CSF. In this study, the chemokine profile demonstrated the following: CNS‐irAE as Th1‐predominant diseases as reported previously 9–13,26 . GFAP‐A was the first to demonstrate a predominance of Th1 + Tfh/B cells, suggesting that cellular immunity is important in its pathogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…Recent findings show that some neurological diseases are related to CXCR3 ligand interactions, which are pivotal in their pathogenesis. 9,12 Further evidence that CXCR3+ cells predominantly infiltrate the spinal fluid or CNS lesions in GFAP-A patients, with a trend toward elevated levels of Th1-dominant chemokines, may indicate that GFAP-A is a Th1-type cell-mediated inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR3 is a 7-transmembrane domain G protein-coupled receptor, which is mainly expressed on immune cells, including T lymphocytes and natural killer cells [14,15]. CXCR3 plays an important role in T cell recruitment in various immune responses and autoimmune diseases [16,17].…”
Section: Introductionmentioning
confidence: 99%